2021
DOI: 10.1101/2021.10.08.463665
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 infection induces inflammatory bone loss in golden Syrian hamsters

Abstract: Extrapulmonary complications of different organ systems have been increasingly recognized in patients with severe or chronic Coronavirus Disease 2019 (COVID-19). However, limited information on the skeletal complications of COVID-19 is known, even though inflammatory diseases of the respiratory tract have been known to perturb bone metabolism and cause pathological bone loss. In this study, we characterized the effects of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection on bone metabolism… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
(66 reference statements)
0
1
0
Order By: Relevance
“… 76 Moreover, a study in hamsters found that SARS-CoV-2 disturbs bone turnover. 77 This bone mechanism disruption may be expected due to the systemic inflammation caused by the cytokine storm. 78 Bone mineral density did not attract that much attention during that pandemic, other than it may be a dangerous severity indicator for COVID patients if it is low.…”
Section: Musculoskeletal (Msk) Symptoms In Long Covidmentioning
confidence: 99%
“… 76 Moreover, a study in hamsters found that SARS-CoV-2 disturbs bone turnover. 77 This bone mechanism disruption may be expected due to the systemic inflammation caused by the cytokine storm. 78 Bone mineral density did not attract that much attention during that pandemic, other than it may be a dangerous severity indicator for COVID patients if it is low.…”
Section: Musculoskeletal (Msk) Symptoms In Long Covidmentioning
confidence: 99%